Management's Right to Manage, A BNA [Bureau of National Affairs] Operations Manual - Dion, Gérard (Relations industrielles / Industrial Relations, 1960)
The article reviews the book, "Management's Right to Manage," by George W. Torrence. A BNA Operations Manual, The Bureau of National Affairs, Inc., Washington 7, D.C., 1959, 109 pp.